Clinical approach: hypokalemia paralysis periodic with type 2 diabetes mellitus and insulin - Wibawa, I. Dewa Gede Amara Putra; Dewi, Anak Agung Istri Sri Kumala (International Journal of Research in Medical Sciences, 2023)
Hypokalemic paralysis periodic (HypoKPP) also known as familial hypokalemic periodic paralysis (FHPP) or primary FHPP is rare case characterized by periodic muscle weakness and estimated prevalence of around 1 in 100.000. Insulin is a treatment for diabetes that also decreases blood potassium levels, therefore, it is necessary to further investigate the causes of hypokalemia. This will be the topic of further discussion if there is a correlation with FHPP. A 32-years-old Indonesian woman with diabetic who has symptoms indicate HypoKPP, and her twin-sister suffered same symptoms is suspected of having FHPP. FHPP is difficult to diagnose due to genetic, other causal factors that must be eliminated, and uncommon references.